Nicotine Oral Administration Attenuates DSS-Induced Colitis Through Upregulation of Indole in the Distal Colon and Rectum in Mice - Nakajima, Akihito; Shibuya, Tomoyoshi; Sasaki, Takashi; Lu, Yu Jie; Ishikawa, Dai; Haga, Keiichi; Takahashi, Masahito; Kaga, Naoko; Osada, Taro; Sato, Nobuhiro; Nagahara, Akihito (Frontiers in Medicine, 2021)
Nicotine affects the gastrointestinal environment and modulates ulcerative colitis (UC). However, the associations among nicotine, gut metabolites, and UC are still largely unknown. We investigated whether orally administered nicotine affected gut metabolites and dextran sodium sulfate (DSS)-induced colitis. C57BL/6 male mice were orally administered nicotine solution in drinking water prior to inducing DSS-induced colitis. Short-chain fatty acids (SCFAs) and indole in gut contents and fecal samples were measured by GC-MS and hydroxylamine-based indole assays, respectively. Oral administration of nicotine increased indole concentration in feces, but, in contrast, SCFA values did not differ with nicotine administration. Indole levels were increased in the distal colon and rectum but not in the cecum and proximal colon. DSS-induced colitis was less severe clinically and histological changes were minimal in the rectum of orally nicotine-administered mice compared to mice drinking only water. 16S rRNA microbiome on the feces revealed an increasing in Clostridium and Porphyromonas in nicotine-administered mice. In conclusion, nicotine administration was associated with increased indole levels in the distal colon and rectum and attenuated DSS-induced colitis. Oral administration of nicotine may play a potential role in indole upregulation and prevention of UC.